Staged open reduction and internal fixation with double-locking plates to treat bilateral distal femur periprosthetic fractures after total knee arthroplasty: A case report - Wu, Jiangpeng; Li, Zheng; Huang, Jiang; Jiao, Xufeng; Cao, Guanglei (Frontiers in Surgery, 2023)
Abstract Background: The incidence of periprosthetic fractures after total knee arthroplasty (TKA) increases in parallel with the number of procedures. Comminuted fractures along the primary fracture line extending to the edge of the prosthesis are challenging, and bilateral fractures are rarely reported, especially with open injuries. Case presentation: A 65-year-old female had undergone bilateral TKA in our hospital 5 years before admission. She was admitted with a traumatic bilateral Rorabeck type II B distal femur periprosthetic fracture (closed right, open left, Gustilo II) and was treated with bilateral staged open reduction and internal fixation (ORIF) with double-locking plates. The patient experienced delayed union and showed signs of concrescence on the right side at 21 months postoperatively. The function was satisfactory after 4 years of follow-up. Conclusion: ORIF with double-locking plates can be used to treat Rorabeck II B periprosthetic fracture where the primary fracture line extends beyond the edge of the prosthesis; however, there may be delayed healing or nonunion. Patients need to undergo long-term rehabilitation and endure long disability times. They require good rehabilitation nursing care. Once they achieve bone healing, the treatment achieves bone preservation and substantial prosthesis survival.